Keadaan bahan kering bibit kelapa sawit dengan aplikasi kompos tankos dan Bacillus sp. - Mira - Ariyanti; Farah - Fadiyah; Santi - Rosniawaty (Paspalum: Jurnal Ilmiah Pertanian, 2023)
Organic fertilizer in the form of compost is possible to be continuesly applied in oil palm plantations, including in nurseries. This is one of the efforts to support the realization of sustainable oil palm plantations. This experiment aims to examine the effect of adding compost made out of empty oil palm bunches (EOPB) and bacteria Bacillus sp. applied either singly or in combination between the two to the state of the dry matter of oil palm seedlings. The experiment was carried out at the Ciparanje Experimental Garden, Faculty of Agriculture, Padjadjaran University from February to May 2022. The experiment was a field test using a randomized block design consisting of nine treatments, repeated three times. The treatments included NPK inorganic fertilizer, Bacillus sp. (25 mL and 35 mL), EOPB compost (100 g, 150 g and 200 g) given to each oil palm seedlings. The experimental results showed that the administration of Bacillus sp. 25 mL/seedling alone had good effect on the dry weight of the roots and dry weight of the oil palm seedlings, while the addition of 150 g/seedling EOPB compost alone had a good effect on the dry weight of the oil palm seedling shoots. The condition of the dry matter of the seedlings with the provision of Bacillus sp. and EOPB compost is as good as oil palm seedlings which are only given NPK fertilizer so that in this case the EOPB compost and Bacillus sp. can be used as an alternative fertilizer to be applied in oil palm nurseries.